Transfer Function and Transient Response Analysis of Active Inrush Current Limiting Circuit on P-MOSFET with Equivalent RLC Series Circuit Load of Inverter - Munnik Haryanti; Adi Nugroho; Bekti Yulianti; Yohannes Dewanto (Dinasti Research, 2024)
Inrush current is a transient current surge when a piece of electrical equipment is turned on. One of the solutions is a P-MOSFET-based active inrush current limiter, which will be analyzed with KiCad software to analyze the transient response graph and a Python program to analyze the transfer function graph. From the observation, the circuit could reduce the inrush current amount which was initially ranging from 12mA – 12A to below 500nA, with a very low amount of ripple (under 100nA peak-to-peak). The transfer function graph from the RLC load represents its transient response graph, and the transfer function graph of the inrush current limiter with load creates a logarithm function. Keywords: inrush current, P-MOSFET, transient response, transfer function, ripple